(untitled) (Global Journal of Human-Social Science, 2017)
The aim of the study was to compare the Brazilian and German social welfare systems, highlighting their similarities and differences and answering the question: have Brazilian social welfare policies moved closer to or farther away from the parent model throughout their historical evolution? The methodology selected for the present study was comparative, with a historical approach. Similarities and differences between the Brazilian social welfare system and Bismarcki an ideals were confirmed, particularly in relation to the failure to incorporate social protagonists in the development of these policies and the involvement of political parties, who serve the interests of distinct social classes, thereby perpetuating the interests of the strongest groups and creating an unequal protection structure and hierarchized benefits. This leads to a population with a low vindicatory performance and reforms that have distinct objectives and are aimed at the private system. Consequently, citizens with equal rights are excluded from the concession of rights and the formation process of these social policies..